Regular Dental Visits: Influence on Health-Related Quality of Life in 1,607 Patients with Oral Squamous Cell Carcinoma - Simon Spalthoff; Henrik Holtmann; Gertrud Krüskemper; Rüdiger Zimmerer; Jörg Handschel; Nils-Claudius Gellrich; Philipp Jehn (International Journal of Dentistry)
Background. The incidence of oral squamous cell carcinoma (OSCC) is in the top 10 of all cancer entities. Regular oral examinations by dentists play an important role in oral cancer prevention. Methods. Patients with OSCC (n=1,607) and physicians (n=1,489) completed questionnaires during the DÖSAK Rehab Study. The psychosocial and functional factors collected in these questionnaires were assessed in the present study. We compared patients who visited their dentist at least once a year (group A) with those who visited their dentist less than once a year (group B). Results. Patients in group A had significantly better health-related quality of life after tumor treatment than patients in group B. Patients in group A also had a smaller tumor size and less lymph node metastasis and lost fewer teeth during the treatment. This resulted in better prosthetic rehabilitation and better psychological status after tumor treatment. Conclusions. Dentists play an important role in the early recognition of oral cancer. This study should encourage dentists to take a more active role in oral cancer prevention.